The Role of Students and Teachers in The Lifecycle of Classrooms in Primary Schools in Indonesia - Satriaji, Kukuh Rizki; Santosa, Imam; Syarief, Achmad; Wibisono, Andriyanto (Journal of Ecohumanism, 2025)
Classrooms play a crucial role facilitating learning activities in schools. The elements present in school classrooms, such as furnitures, walls, bulletin boards, posters, attendance schedules, colors, and learning models, provide identity and experiences for students. The arrangement of these elements enables classroom users to identify their functions. The education system in Indonesia allocates students to use the same classroom for approximately one academic year at each level. Users of the classroom have the flexibility to make changes and adaptations within it. This study identifies the changes occurring within classrooms and their reasons and influences on the implementation of learning in elementary schools. The research focuses on three elementary schools in Indonesia that employ an active learning system utilizing classroom area. The methods used include classroom observations, teacher interviews, and distribution of questionnaires to elementary school 4th to 6th grade students. The findings reveal that students and teachers strive to create comfortable learning activities by making various adaptation in their classroom, which categorized as classroom personalized adaptation purpose, learning functional purpose, and decorative purpose. These findings provide opportunities for teachers, school management, and researchers to reconsider the potential of classrooms, thus utilizing them as comfortable spaces for students to use during the learning activities.